Unique Fixed Point Theorems for Generalized Contractive Mappings in Partial Metric Spaces. (5th October 2015) - Mishra, Lakshmi Narayan; Tiwari, Shiv Kant; Mishra, Vishnu Narayan; Khan, Idrees A.
Abstract : We establish some unique fixed point theorems in complete partial metric spaces for generalized weaklyS -contractive mappings, containing two altering distance functions under certain assumptions. Also, we discuss some examples in support of our main results.